Entitlement to Sickness Benefits in Sweden: The Social Insurance Officers Experiences - Ulrika Müssener; Elsy Söderberg (SAGE Publishing, 2008)
Background: Social insurance offices (SIOs) handle a wide range of complex assessments of the entitlement to sickness benefits for an increasing number of clients on sick leave and consequently, the demands on the SIOs have increased considerably.Aim: To gain deeper knowledge of the problems experienced by the SIOs in their work associated with entitlement to sickness benefits.Method: A descriptive and explorative qualitative approach was used to analyse data from two focus-group interviews, including six participants in each group.Results: The participants discussed different dilemmas in regard to; physicians' responsibility for issuing sickness certificates, interactions with the insured individuals, disclosure of decisions, communications with medical consultants, documentation of sickness benefit claims, threats in the workplace, as well as their own competence. The SIOs regarded incomplete information on sickness certificates as a main problem, because they frequently had to contact the client and the physicians who issued the certificates in order to obtain further details, leading to delays in the decision-making whether to grant sickness benefits.Conclusions: More knowledge regarding SIOs work is required to improve the methods used in the sickness insurance system and to ensure adequate training of new staff members.